FINANCIAL PERFORMANCE, AUDIT DELAY AND FIRM VALUES BANKING IN INDONESIA - Stephanus Dwiarso Utomo; Maradewi Ayu Kumalasari; Zaky Machmuddah (University of Merdeka Malang, 2017)
Fraud cases in the capital market concerning financial report delay were the main issues of the research. The aim of this research was to investigate the effect of financial performance, audit delay, and firm value. The population of the research was all companies listed in Indonesian Stock Exchange, from 2011-2013. The total of research samples were 38 banking companies with 97 annual reports done by using purposive sampling method. Data analyses used were classical assumption test and hypothesis test with multiple-linear regression analysis. The result of the research showed that financial performance had a significant influence on audit delay, while financial performance had a significant influence on firm value. Meanwhile, audit delay did not significantly influence firm value. The practical implication of the research suggested the delay of the financial report’s delivery had an impact on a company’s image in front of the stakeholders.